2000
DOI: 10.1177/002215540004800611
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Different Antibodies for Immunohistochemical Localization of CFTR in Sweat Glands from Healthy Controls and from Patients with Cystic Fibrosis

Abstract: S U M M A R YThe hereditary disease cystic fibrosis (CF) is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. Understanding of the consequences of CFTR gene mutations is derived chiefly from in vitro studies on heterologous cell cultures and on cells hyperexpressing CFTR. Data from ex vivo studies on human tissue are scarce and contradictory, a fact which is in part explained by secondary tissue destruction in most affected organs. The purpose of this study was to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
(41 reference statements)
1
23
2
Order By: Relevance
“…The ratio of CFTR band B to band C was also unaltered, suggesting that CFTR maturation and glycosylation were not grossly affected by NHERF-1 ablation. Furthermore, confocal microscopy showed no evidence for an alteration in the localization of CFTR in jejunal crypts of NHERF-1 Ϫ/Ϫ mice, but it should be added that not all CFTR present in the cell is detected by this technique; in general, even the best CFTR antibodies fail to detect CFTR in the endoplasmic reticulum and Golgi, although it is known to be present there as well (42). Based on analysis of CFTR abundance in jejunal crypts by confocal microscopy, we estimate that the mean fluorescence intensity and the total level of fluorescence per crypt were reduced by ϳ35% in NHERF-1-and NHERF-1/2-deficient mice.…”
Section: Discussionmentioning
confidence: 94%
“…The ratio of CFTR band B to band C was also unaltered, suggesting that CFTR maturation and glycosylation were not grossly affected by NHERF-1 ablation. Furthermore, confocal microscopy showed no evidence for an alteration in the localization of CFTR in jejunal crypts of NHERF-1 Ϫ/Ϫ mice, but it should be added that not all CFTR present in the cell is detected by this technique; in general, even the best CFTR antibodies fail to detect CFTR in the endoplasmic reticulum and Golgi, although it is known to be present there as well (42). Based on analysis of CFTR abundance in jejunal crypts by confocal microscopy, we estimate that the mean fluorescence intensity and the total level of fluorescence per crypt were reduced by ϳ35% in NHERF-1-and NHERF-1/2-deficient mice.…”
Section: Discussionmentioning
confidence: 94%
“…MATG1061 showing markedly less background staining than 169. Although MATG1061 has been applied successfully in several studies of airway cells (Puchelle et al 1992;Jacquot et al 1993;Brezillon et al 1995;Dupuit et al 1995;Kälin et al 1999), Claass et al (2000) demonstrated that MATG1061 was nonspecific for CFTR in the sweat glands. However, these authors employed an IHC analysis using an enhanced enzymatic alkaline phosphatase-anti-alkaline phosphatase (APAAP) (Cordell et al 1984) and not an immunofluorescence one.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible reasons why our data and conclusions differ from some previous reports. First, our mAbs exhibit very high affinity for CFTR and hence may be less cross-reactive with other apical PM proteins in the CF lung compared with CFTR antibodies (Claass et al, 2000) used in previous studies (Kalin et al, 1999;Penque et al, 2000;Carvalho-Oliveira et al, 2004). Second, we applied multiple, complementary techniques to the same specimens.…”
Section: Expression Of ⌬F508 Cftr In Cf Airway Epitheliamentioning
confidence: 99%